The Morphological and Hemodynamic Characteristics of the Intraoperative Ruptured Aneurysm - Liu, Qingyuan; Jiang, Pengjun; Wu, Jun; Gao, Bin; Wang, Shuo (Frontiers in Neuroscience, 2019)
Background and Objectives: Intraoperative aneurysm rupture (IOR) is a tough event during the clipping process for intracranial aneurysms, and it could result in a bad prognosis. Preoperative discrimination of aneurysms with high risk of IOR is vital for operators. The aim of this study was to explore the hemodynamic-morphological risk factors for the IOR. Methods: In the present study, patients admitted for unruptured IA from January 2012 to April 2018 were retrospectively reviewed. A propensity score matching was performed to match patients. The morphological features and the hemodynamic features were extracted. Differences in the morphologic and hemodynamic parameters were compared. Risk factors associated with IOR were explored. Subsequently, the hemodynamic characteristics in different rupture stages and different regions in IOR aneurysm were compared. Results: 96 aneurysms were yielded by matching process in each group. The statistically significant difference was found in maximum length (L) (p=0.041), maximum diameter of body (D) (p=0.032), aspect ratio (AR) (p<0.001), nonsphericity index (NSI) (p<0.001), normalized wall shear stress maximum (NWSSm) (p<0.001) and oscillatory shear index (OSI) (p<0.001). A regression analysis demonstrated AR (OR=7.03, p<0.001), NWSSm (OR=15.55, p=0.014) and OSI (OR=28.30, p<0.001) as the independent risk factors for IOR. AR was much larger, and NWSSm and NWSSa were much lower for IAs ruptured in early or pre-dissection stage than those for IAs ruptured in dissection stage or clip application stage. NWSSa and NWSSm in rupture area were both lower than those in adjacent area. Conclusion: AR, NWSSm and OSI were considered three independent risk factors for intraoperative aneurysm rupture, which could serve as predictors. Selection of intervention methods for aneurysms with high AR, low NWSSm and high OSI should be carefully considered.